Enforcement of Criminal Law on Marine Traffic Negligence in Indonesia: Perspectives of Law No. 17/2008 - Koswara, Indra Yudha; Faridah, Hana (Transactions on Maritime Science, 2023)
Sea transportation must be integrated and able to create a safe transportation service provider. It must have high accessibility, integrated services, adequate capacity, be orderly, easily accessible, timely, comfortable, and efficient. This paper analyzes national shipping safety and security standards as a form of legal protection for the users. The study describes the implementation of standards for the regulation of shipping safety and security, and the process of law enforcement against ship accidents for perpetrators and ship owners, based on illegal acts. In this research, providing regulations and enforcing the regulations must be relevant to the conditions in the field. The government has provided regulations on shipping safety and security. The shipowner or ship operator is responsible for following the Regulation of the Minister of Transportation. RI No. 6/2020 concerning the Procedures for Investigation of Ship Accidents, Chapter V Responsibility Due to Ship Accidents, Article 61 Ships, and according to legal principles in Article 1356 of the Civil Code, for legal protection of the passengers using National Shipping services.